The Effect of Profitability, Managerial Ownership and Dividend Policy on Company Value on Property Companies Listed on the Indonesia Stock Exchange - Marzuki, Marzuki; Akhyar, Chairil; Zahrina, Zahrina (Universitas Batam, 2020)
The purpose of this study was to examine the effect of profitability, managerial ownership and dividend policy on company value on property companies listed on the Indonesia Stock Exchange. The data used in this research were ROE, KM, DPR and PBV data on property companies in Indonesia Stock Exchange during 2016-2021. The data of this study were accessed on www.idx.co.id and www.bi.go.id. The method of data analysis in this study was multiple linear regression analysis. The results of the study found that Profitability (ROE) and Dividend Policy (DPR) had a positive and significant effect on company value, while managerial ownership had a negative effect on company value. The simultaneous test results found that profitability, managerial ownership, and dividend policy had a significant effect on company value.